Protocol- Comprehensive Care Package to reduce deaths among adult persons diagnosed with Tuberculosis in Kerala, India (CCp-K)-An implementation project - Raman Swathy Vaman; Kalaiselvi Selvaraj; Dina Nair; Abey Sushan; Aparna Mohan; Krishna Devadhas Sulochana; Jeen Melfha; Arun Paramarthalingom Vijayalekshmi; Vyas Sukumaran; Naveen Anaswara; Sujith Sukumaran; Annadurai Jeyakumar; et al. (MethodsX)
This implementation project aims to reduce TB mortality by at least 25% through early triaging and integrated management of co-morbidities in Kerala, India. The package will be implemented across Kerala’s public health facilities, targeting all adult TB patients for systematic triaging for severe illness, uncontrolled diabetes mellitus, alcohol dependence, and tobacco dependence. Triage-positive individuals will be referred for comprehensive assessment and inpatient care to nodal treatment centres. This research will follow a mixed-methods approach with quantitative components assessing feasibility, burden, and programmatic outcomes, and qualitative interviews exploring facilitators and barriers. Triaging will be integrated into routine workflows with healthcare worker training and system monitoring using customized indicators. If found feasible and effective in improving programmatic outcomes such as early triaging and inpatient referral, this model offers potential for scale-up across India to reduce preventable TB deaths through differentiated care and targeted comorbidity management.• Implements a comprehensive care package to reduce TB deaths through early triaging and comorbidity management• Leverages existing public health infrastructure to deliver enhanced TB care within routine programme settings